2018
DOI: 10.1371/journal.pone.0194613
|View full text |Cite
|
Sign up to set email alerts
|

Complete chloroplast genome of seven Fritillaria species, variable DNA markers identification and phylogenetic relationships within the genus

Abstract: Fritillaria spp. constitute important traditional Chinese medicinal plants. Xinjiang is one of two diversity hotspots in China in which eight Fritillaria species occur, two of which are endemic to the region. Furthermore, the phylogenetic relationships of Xinjiang Fritillaria species (including F. yuminensis) within the genus are unclear. In the present study, we sequenced the chloroplast (cp) genomes of seven Fritillaria species in Xinjiang using the Illumina HiSeq platform, with the aim of assessing the glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 54 publications
15
32
0
Order By: Relevance
“…Our results revealed that the whole plastome sequences of 11 newly sequenced Fritillaria species were conserved not only in genome size, but also in gene content, structure, and order (Figure 1), which was consistent with previously published Fritillaria plastomes studies [23][24][25]. Nevertheless, some CDS genes exhibited high variations, mainly in some pseudogenes, for example ψycf15, ψycf68, and ψinfA, which were also reported in other angiosperm plastid genomes [7,9,26,27].…”
Section: Comparison Of Fritillaria Plastomes and Phylogenetically Infsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results revealed that the whole plastome sequences of 11 newly sequenced Fritillaria species were conserved not only in genome size, but also in gene content, structure, and order (Figure 1), which was consistent with previously published Fritillaria plastomes studies [23][24][25]. Nevertheless, some CDS genes exhibited high variations, mainly in some pseudogenes, for example ψycf15, ψycf68, and ψinfA, which were also reported in other angiosperm plastid genomes [7,9,26,27].…”
Section: Comparison Of Fritillaria Plastomes and Phylogenetically Infsupporting
confidence: 90%
“…It is worth noting that there are only F. crassicaulis, F. dajinensis, F. delavayi, F. sichuanica, and F. unibracteata having ψycf15 and ψycf68 in our results, indicating a few common aspects in their evolutionary processes and functions. The absence or presence of ψycf15 and ψycf68 in other Fritillaria species has also been reported by Li et al [25]. The same phenomenon has also been observed in Ipomoea [28].…”
Section: Comparison Of Fritillaria Plastomes and Phylogenetically Infsupporting
confidence: 81%
See 1 more Smart Citation
“…(Ahmed et al, 2013; Ahmad, 2014; Nguyen et al, 2017). Previously, in several studies, polymorphic loci were identified based on comparisons of chloroplast genome to provide information about suitable loci for the development of molecular markers (Choi, Chung & Park, 2016; Li et al, 2018; Menezes et al, 2018). We found 20 polymorphic regions such as infA, rps12 intron, rps16-trnQ-UUG which have 0.25942, 0.15275, 0.08451 nucleotide diversity respectively that were more polymorphic than frequently used markers such as rbcL , and matK .…”
Section: Discussionmentioning
confidence: 99%
“…The whole‐chloroplast genome is termed a “super‐barcode” and provides more abundant informative sites for species identification. These super‐barcodes exhibit higher discrimination power for closely related species and have been applied for the identification of species in various taxa, such as the genera Fritillaria (Li, Zhang, Yang, & Lv, ), Epipremnum (Tian, Han, Chen, & Wang, ), and Papaver (Zhou et al, ). The use of a super‐barcodes is a good option for the identification of closely related Corydalis species and obtaining improved species discrimination power.…”
Section: Discussionmentioning
confidence: 99%